Updating global estimates of pathogen-attributable diarrhoeal disease burden: a methodology and integrated protocol for a broad-scope systematic review of a syndrome with diverse infectious aetiologies - Margaret N Kosek; Brecht Devleesschauwer; Shannon E Majowicz; Josh M Colston; Thomas G Flynn; Andrea H Denton; Francesca Schiaffino; Carlotta Di Bari; Yuki Minato (BMJ Open)
Introduction Sustaining declines in global infectious disease burden will increasingly require efforts targeted to specific aetiological agents and common transmission pathways, particularly in this era of global change and human interconnectivity accelerating transmission and emergence of infectious pathogens. Systematic reviews and meta-analyses can be an effective and resource-efficient method for synthesising evidence regarding disease epidemiology for a wide range of pathogens and are the evidence source used by initiatives like the Planetary Child Health and Enterics Observatory (Plan-EO) and the WHO to determine the aetiology-specific epidemiology of diarrhoeal disease. Therefore, we developed this integrated systematic review methodology and protocol that aims to compile a database of published prevalence estimates for 17 diarrhoea-causing pathogens as inputs for disease burden estimation.Methods and analysis We will seek estimates of the prevalence of each endemic enteric pathogen estimated from published population-based studies that diagnosed their presence in stool samples from both asymptomatic subjects and those experiencing diarrhoea. The pathogens include the enteric viruses adenovirus, astrovirus, norovirus, rotavirus and sapovirus, the bacteria Campylobacter, Shigella, Salmonella enterica, Vibrio cholerae and the Escherichia coli (E. coli) pathotypes enteroaggregative E. coli, enteropathogenic E. coli, enterotoxigenic E. coli and Shiga-toxin-producing E. coli and the intestinal protozoa Cryptosporidium, Cyclospora, Entamoeba histolytica and Giardia. Meta-analytical methods for analyses of the resulting database (including risk of bias analysis) will be published alongside their findings.Ethics and dissemination This systematic review is exempt from ethics approval because the work is carried out on published documents. The database that results from this review will be made available as a supplementary file of the resulting published manuscript. It will also be made available for download from the Plan-EO website, where updated versions will be posted on a quarterly basis.PROSPERO registration number CRD42023427998.